FENOMENA KEKERASAN SEBAGAI BENTUK KEJAHATAN (VIOLENCE) - Anjari, Warih (E-Journal Widya Yustisia, 2017)
Sometimes man, as social creatures, in interacting with others create conflict either in the way or the goal, resulting violence. At the end of 2012 and beginning of 2013, there was an increase of violence in Indonesian society which occurs in education institution, and also between the state apparatus. The purpose of this writing are: (1) to discuss the violence as a form of crime from the point of the view of the Indonesian legal system (2) to analyze the causes of violence as a form of crime from anthropological, sociological and psychological approaches. The method applied is library research with the descriptive and explorative approach and the data were analyzed with qualitative methods. It can be concluded that: (1) Violence is a form of crime. In the Indonesian legal system can be punished by the Penal Code and Special Offens. (2) Causative factor is heterogeneous culture, different acculturation, social jealousy (antropology); deviant behaviour and the process of stigmatization (sosiology);imitation and mental disorders (pshicology). It recommended for law enforcement needs to be improved through the application of strict sanction and change the mind set towards non-violence.